2005
DOI: 10.1111/j.1601-183x.2005.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule (NCAM –/– ) null mice show impaired sensitization of the startle response

Abstract: The neural cell adhesion molecule (NCAM) plays important roles in development of the nervous system and in synaptic plasticity and memory formation in the adult. The present study sought to further investigate the role of NCAM in learning by testing habituation and footshock sensitization learning of the startle response (SR) in NCAM null mutant (NCAM -/-) and wildtype littermate (NCAM +/+ ) mice.Whereas habituation is a form of non-associative learning, footshock sensitization is induced by rapid contextual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…CD49a corresponds to the α 1 integrin subunit and has been found associated with MSCs from synovium [38]. CD56 was identified as a neural cell adhesion molecule [39] and MSCA-1 as a tissue nonspecific alkaline phosphatase [40]. Interestingly, Battula et al [41] have shown that the subpopulation of BM-MSCs coexpressing CD56 and MSCA-1 presents strong chondrogenic differentiation capability whereas the MSCA-1 + /CD56 − subpopulation can differentiate into adipocytes only.…”
Section: Discussionmentioning
confidence: 99%
“…CD49a corresponds to the α 1 integrin subunit and has been found associated with MSCs from synovium [38]. CD56 was identified as a neural cell adhesion molecule [39] and MSCA-1 as a tissue nonspecific alkaline phosphatase [40]. Interestingly, Battula et al [41] have shown that the subpopulation of BM-MSCs coexpressing CD56 and MSCA-1 presents strong chondrogenic differentiation capability whereas the MSCA-1 + /CD56 − subpopulation can differentiate into adipocytes only.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the NCAM gene in NCAM knock-out (NCAM KO) mice leads to impaired LTP at CA1 and at mossy fiber synapses in CA3 hippocampal areas (Cremer et al, 1998;Muller et al, 2000). In addition, NCAM KO mice have been reported to show severe cognitive impairments and emotional alterations, including: (i) impaired spatial learning and memory (Cremer et al, 1994;Stork et al, 2000), (ii) impaired auditory and contextual fear conditioning (Senkov et al, 2006;Stork et al, 2000), (iii) impaired odor discrimination (Gheusi et al, 2000), (iv) enhanced anxiety (Cremer et al, 1994;Stork, Welzl, Cremer, and Schachner, 1997;Stork et al, 1999), (v) reduced footshock sensitization in the startle response (Plappert, Schachner, & Pilz, 2006), (vi) enhanced exploratory behavior (Stork, Welzl, Cremer, & Schachner, 1997;Stork et al, 1999), (vii) enhanced inter-male aggression towards an intruder (Stork et al, 1997(Stork et al, , 2000 and (viii) increased corticosterone levels following social intruder stress (Stork et al, 1997). Moreover, these NCAM KO mice show also mild morphological alterations in the CNS, including a reduction in brain weight and size of the olfactory bulb (Cremer et al, 1994) and an altered cytoarchitecture of the hippocampus (Cremer, Chazal, Goridis, & Represa, 1997;Tomasiewicz et al, 1993).…”
Section: Ncammentioning
confidence: 99%
“…26 Other reports demonstrated a 9.5-fold enrichment of MSC in bone marrow cells with prominent aldehyde dehydrogenase activity. 27 Recently, we have shown that CD56, a marker for natural killer, neural, and muscle cells, [28][29][30] is additionally expressed on a small subset of bone marrow CD271 bright cells. 26 We also demonstrated that W8B2 antigen 31 (here designated mesenchymal stem cell antigen-1; MSCA-1) is selectively expressed on CD271 bright bone marrow cells and hypothesized that W8B2 antibody reacts with CFU-F, as these clonogenic cells are known to reside in the CD271 bright population.…”
Section: Introductionmentioning
confidence: 99%